Implementasi Model Supervisi Distributif dalam Meningkatkan Profesionalisme Guru PAI: (Studi Kasus di Kecamatan Long Ikis) - Suparmin, Suparmin; Adiyono, Adiyono (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
This study aims to explore and apply the distributive supervision model in improving the professionalism of Islamic Religious Education teachers in Long Ikis sub-district. Managerial supervision has long been used as an approach in helping to improve the quality of teaching and learning. However, the success of managerial supervision in providing appropriate and ongoing support for teachers remains a major concern. Therefore, this study offers a distributive supervision model as an interesting and innovative alternative to improve the effectiveness of supervision in the field of Islamic Religious Education. This study used a qualitative approach involving teachers, principals and Islamic Religious Education supervisors as informants. Data were obtained through in-depth interviews, classroom observations, and document analysis related to academic supervision. The results showed that the implementation of the distributive supervision model has made a significant contribution in improving the professionalism of Islamic Religious Education teachers in Long Ikis sub-district.Keyword: Distributive Supervision; School Superintendent; PAI Professionalism Teachers.